Molar mass and temperature dependence of rheological properties of polymethylmethacrylate melt - Lu, Zhili; Pan, Yamin; Liu, Xianhu; Zheng, Guoqiang; Schubert, Dirk W.; Liu, Chuntai (Materials Letters, 2018)
The influence of molar mass and temperature on the rheological properties of polymethylmethacrylate (PMMA) melts was investigated by dynamical mechanical and creep-recovery experiments. The results shown that the steady state viscosities obtained from both experimental modes were in good agreement, and a well linear relationship between the activation energy and molar mass was obtained. The creep compliance of PMMA increased with the molar mass increased or temperature decreased, while the linear steady state recoverable compliance was found to be independent of the molar mass and temperature. Moreover, it was found that the master curves followed the time-temperature superposition principle well in the whole frequency range or time scal
Keywords: Amorphous materials; Creep; Activation energy; Molar mass; Viscosity